Isoprene–Styrene Chain Shuttling Copolymerization Mediated by a Lanthanide Half‐Sandwich Complex and a Lanthanidocene: Straightforward Access to a New Type of Thermoplastic Elastomers1. (25th March 2014) - Valente, Andreia; Stoclet, Gregory; Bonnet, Fanny; Mortreux, André; Visseaux, Marc; Zinck, Philippe
Abstract A lanthanide half‐sandwich complex and a ansa lanthanidocene have been assessed for isoprene–styrene chain shuttling copolymerization with n‐butylethylmagnesium (BEM). In the presence of 1 equiv BEM, a fully amorphous multiblock microstructure of soft and hard segments is achieved. The microstructure consists of poly(isoprene‐co‐styrene) blocks, with hard blocks rich in styrene and soft blocks rich in isoprene. The composition of the blocks and the resulting glass transition temperatures (Tg) can be easily modified by changing the feed and/or the relative amount of the catalysts, highlighting a new class of thermoplastic elastomers (TPEs) with tunable transition temperatures. The materials self‐organize into nanostructures in the solid state.